Evolution and transmission dynamics of wild poliovirus in Pakistan and Afghanistan (2012-2023) - David Jorgensen; Margarita Pons-Salort; Muhammad Salman; Adnan Khurshid; Yasir Arshad; Nayab Mahmood; Darlan da Silva Candido; Steve Kroiss; Hil Lyons; Nicholas C. Grassly; Muhammad Masroor Alam (Nature Communications)
Abstract Despite concerted global vaccination efforts, wild poliovirus remains endemic in two countries in 2024, Pakistan and Afghanistan. This study uses phylogeographic analysis of poliovirus genetic and epidemiological data from clinical and wastewater surveillance to identify the causes of poliovirus persistence and routes of spread over the last decade (2012 to 2023). Poliovirus genetic diversity declined after 2020, with one of two major genetic clusters dying out, and recent detections are now closely related genetically. High-risk and hard-to-access regions have sustained polio transmission over the past decade, even when interrupted elsewhere. Karachi, one of the most densely populated cities globally, has acted as a hub for the amplification and spread of poliovirus to other regions, many of which we show to be dead-end for onwards transmission despite frequent virus detection. Phylogenetic analysis has long been central to the polio surveillance network, and advancing the approaches used can provide critical epidemiological insights to accelerate eradication efforts.